PEMBUATAN MEDIA PEMBELAJARAN BERBASIS TIK UNTUK PENGEMBANGAN E-LEARNING SISTEM BAGI GURU: STUDI PADA GURU-GURU SMP MUHAMMADIYAH 14 PACIRAN LAMONGAN - Philipus Keban; Yayan Sakti Suryandaru; Nanang Haryono (Jurnal Layanan Masyarakat (Journal of Public Services), 2021)
Learning media is an important part of the distance learning process, especially in the midst of the Covid-19 pandemic. Online learning implemented in the midst of a pandemic demands innovation. The process of learning media innovation with the use of information technology is a big part of the progress of education. E-learning as a learning model in education provides a big role and function for the world of education. E-learning as a distance learning model in the education sector provides a big function and role for the world of education, especially since the Indonesian Government since March 2, 2020 (kompas.com) is facing the Covid-19 outbreak where all students at all levels are studying at home. Teachers at all levels of education as the spearhead of the implementation of education need to be empowered by providing knowledge and skills in making innovative learning media using technology. Community service that has been carried out aims to empower teachers in making technology-based learning media. This is based on the special problems faced by teacher partners (SMP Muhammadiyah 14 Paciran), the difficulty in making innovative learning media using technology. After empowerment through lectures on the importance of e-learning, followed by training on innovative learning media with movavi, and direct assistance and use of zoom, it was concluded that (a) teacher partners of SMP Muhammadiyah 14 Pondok Pesantren Karangasem Lamongan have increased knowledge (b) Teachers are capable converting PPT into visual learning media using Movavi software, (c) The teacher is able to take pictures, edit using Movavi on a smartphone. (d) At this stage the teachers are able to make learning media starting from planning by selecting important materials, taking pictures, editing learning media, to rendering so as to produce learning media that attracts students. abstrakMedia pembelajaran menjadi bagian penting dalam proses pembelajaran jarak jauh terlebih ditengah pandemi covid-19. Pembelajaran daring yang diimplementasi ditengah pandemi menuntut inovasi. Proses inovasi media pembelajaran dengan penggunakaan teknologi informasi bagian besar untuk kemajuan Pendidikan. E-learning sebagai model pembelajaran dalam pendidikan memberikan peran dan fungsi yang besar bagi dunia pendidikan. E-learning sebagai model pembelajaran jarak jauh sektor pendidikan memberikan fungsi dan peran yang besar bagi dunia pendidikan lebih-lebih saat ini Pemerintah Indonesia sejak 2 Maret 2020 (kompas.com) menghadapi wabah covid-19 dimana semua siswa pada semua jenjang belajar dirumah. Guru pada semua jenjang pendidikan sebagai ujung tombak pada pelaksanaan Pendidikan perlu diberdayakan dengan memberi bekal pengetahuan, ketrampilan dalam membeuat media pembelajaran yang inovatif dengan pemanfaatan teknologi. Pengabdian masyarakat yang telah dilaksankaan bertujuan untuk pemberdayaan guru dalam membuat media pembelajaran berbasis teknologi. Hal tersebut didasari permasalahan khusus yang dihadapi mitra guru (SMP Muhammadiyah 14 Paciran) kesulitan dalam pembuatan media pembelajaran inovatif dengan penggunaan teknologi. Setelah dilaksankaan pemberdayaan melalui ceramah pentingnya pembelajaran e-learning, dilanjutkan dengan pelatihan inovasi pembaatan media pembelajaran dengan movavi, dan pendampingan baik melalui langsung dan penggunaan zoom disimpulkan (a)  mitra guru SMP Muhammadiyah 14 Pondok Pesantren Karangasem Lamongan  telah bertambah pengetahuannya (b) Guru mampu mengubah PPT menjadi media pembelajaran visual dengan menggunakan software movavi, (c) Guru mampu untuk pengambilan gambar, editing menggunakan movavi pada smartphone. (d) Pada tahap ini guru-guru mampu membuat media pembelajaran mulai dari perencanaan dengan memilih materi penting, pengambilan gambar, melaksanakan editing media pembelajaran, sampai rendering sehingga menghasilkan media pembelajaran menarik siswa.